Simulation of Magnetically Dispersed Arc Plasma - 白冰 查俊 张晓宁 王城 夏维东 (Plasma science & technology, 2012)
Magnetically dispersed arc plasma exhibits typically dispersed uniform arc column as well as diffusive cathode root and diffusive anode root. In this paper magnetically dispersed arc plasma coupled with solid cathode is numerically simulated by the simplified cathode sheath model of LOWKE . The numerical simulation results in argon show that the maximum value of arc root current density on the cathode surface is 3.5×10^7 A/m^2）, and the maximum value of energy flux on the cathode surface is 3× 10^7 J/m^2, both values are less than the average values of a contracted arc, respectively.